2015
DOI: 10.1371/journal.pcbi.1003981
|View full text |Cite
|
Sign up to set email alerts
|

Highly Loaded Behavior of Kinesins Increases the Robustness of Transport Under High Resisting Loads

Abstract: Kinesins are nano-sized biological motors which walk by repeating a mechanochemical cycle. A single kinesin molecule is able to transport its cargo about 1 μm in the absence of external loads. However, kinesins perform much longer range transport in cells by working collectively. This long range of transport by a team of kinesins is surprising because the motion of the cargo in cells can be hindered by other particles. To reveal how the kinesins are able to accomplish their tasks of transport in harsh intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Earlier theoretical studies have modeled cargo transport by multiple motors [21][22][23][24][25] but have not been able to predict the experimentally observed velocities and run times (average time to detachment) at high forces [17]. These models all assumed a symmetric force-detachment rate relation for a single kinesin; i.e., the detachment rate under assisting forces (applied in the stepping direction, positive) is equal to that under resisting or loading forces (applied against the stepping direction, negative).…”
mentioning
confidence: 99%
“…Earlier theoretical studies have modeled cargo transport by multiple motors [21][22][23][24][25] but have not been able to predict the experimentally observed velocities and run times (average time to detachment) at high forces [17]. These models all assumed a symmetric force-detachment rate relation for a single kinesin; i.e., the detachment rate under assisting forces (applied in the stepping direction, positive) is equal to that under resisting or loading forces (applied against the stepping direction, negative).…”
mentioning
confidence: 99%
“…Then, the unbinding probability of kinesin per step can be calculated by using A int as where is the unbinding probability per step when every neighboring binding site is not occupied by obstacles. are obtained from our previous model [ 45 ]. Δ P ub, obs is the change in the unbinding probability due to obstacles.…”
Section: Resultsmentioning
confidence: 99%
“…Δ P ub, obs is the change in the unbinding probability due to obstacles. Note that the kinesin dissociates from the MT mostly when one of its heads is diffusing [ 10 , 45 ]. Thus, it is assumed that the increase of the unbinding probability due to obstacles during that diffusion is also very large compared to Δ P ub, obs for other kinesin states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors proposed that the increased run-length observed in the presence of two motors results from the lowered dissociation of each motor from the microtubule at decreased ATP concentrations and the increased probability that the cargo stayed bound to the microtubule. Studies such as [21, 29] using probabilistic models of single motors have also predicted in that an ensemble of kinesin motors is a robust system and the robustness increases under high loads [37]. …”
Section: Introductionmentioning
confidence: 99%